Severe scratcher-reaction: an unknown health hazard? - Carsten Sauer Mikkelsen; Helene Ringe Holmgren; Kristian Bakke Arvesen; Reem Dina Jarjis; Gudjon Leifur Gunnarsson (PAGEPress Publications, 2015)
Tattoos are well known to cause skin problems and the number of reported adverse reactions after tattooing has increased. Illegally imported tattoo ink is unrestrained and can contain unknown ingredients and contamination thereby posing a serious health hazard. We present a case illustrating the risk of pronounced phototoxic allergic reaction and other severe complications after using home kit tattoo ink.